2002
DOI: 10.1111/j.1349-7006.2002.tb01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nucleotide Excision Repair by Fludarabine in Normal Lymphocytes in vitro, Measured by the Alkaline Single Cell Gel Electrophoresis (Comet) Assay

Abstract: Alkylating agents or platinum analogues initiate several excision repair mechanisms, which involve incision of the DNA strand, excision of the damaged nucleotide, gap filling by DNA resynthesis, and rejoining by ligation. The previous study described that nucleotide excision repair permitted incorporation of fludarabine nucleoside (F-ara-A) into the repair patch, thereby inhibiting the DNA resynthesis. In the present study, to clarify the repair kinetics in view of the inhibition by Fara-A, normal lymphocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…It is known that alkylated bases initiate several excision repair mechanisms, which involve incision of the DNA strand, excision of the damaged nucleotide, gap filling by DNA resynthesis, and rejoining by ligation (Yamauchi et al 2002). Thus, another way to detect the overall effects on DNA damage induced by alkylating agents is by using DNA repair inhibitors interfering the repair mechanism that eliminated DNA alkylations.…”
Section: Discussionmentioning
confidence: 98%
“…It is known that alkylated bases initiate several excision repair mechanisms, which involve incision of the DNA strand, excision of the damaged nucleotide, gap filling by DNA resynthesis, and rejoining by ligation (Yamauchi et al 2002). Thus, another way to detect the overall effects on DNA damage induced by alkylating agents is by using DNA repair inhibitors interfering the repair mechanism that eliminated DNA alkylations.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that fludarabine is capable of inhibiting DNA repair induced by carboplatin 33 or UV radiation 34 in quiescent human lymphocytes that were stimulated by 4-hydroperoxycyclophosphamide in CLL lymphocytes, 23 and cisplatin-generated damage in K562 cells. 26 As an extension of those studies, the present investigations reveal a greater than additive cytotoxic effect of fludarabine in combination with oxaliplatin in both normal lymphocytes and CLL cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Comet assay was used for this purpose according to the method previously described, with a slight modification. 16) Briefly, lymphocytes after treatments were mixed with agarose and placed onto a microscope slide. After solidification of the agarose, the slide was left in a lysis solution (2.5 M NaCl, 10 mM Tris, 100 mM ethylenediaminetetraacetic acid, 10% dimethylsulfoxide, and 1% Triton X-100, pH 10) for 1 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…15,16) In brief, normal lymphocytes (2×10 6 cells) having previously been treated and washed in fresh media were incubated with tritiated thymidine (3 µCi/ml) for 0, 1, 2, 4, and 6 h. The lymphocytes were then collected, centrifuged, and resuspended in 500 µl of 0.4 N perchloric acid. The sample was mixed, centrifuged, and resuspended again in the acid.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation